2020
DOI: 10.1039/c9tb02610j
|View full text |Cite
|
Sign up to set email alerts
|

In situ self-assembled Ag–Fe3O4 nanoclusters in exosomes for cancer diagnosis

Abstract: We have utilized HepG2 cancer cells for the in situ biosynthesis of silver and iron oxide nanoclusters. The self-assembled nanoclusters loaded on exosomes could be utilized to bioimage cancer through fluorescence imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In this ScR, we found that the variety of NMs exposed to the different biological models increased exosome secretion (see Figure 3 B), whereas no significant differences were observed regarding their size or morphology [ 26 , 39 , 40 , 41 , 44 , 45 , 46 , 49 , 51 ]. Many studies reported vesicles with a cup-shaped appearance in the negative-stain TEM with HSP 70, CD63, CD81, CD9, LAMP1, and TSG101 as characteristic markers, suggesting that the vesicular secretome that was isolated also comprised exosomes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In this ScR, we found that the variety of NMs exposed to the different biological models increased exosome secretion (see Figure 3 B), whereas no significant differences were observed regarding their size or morphology [ 26 , 39 , 40 , 41 , 44 , 45 , 46 , 49 , 51 ]. Many studies reported vesicles with a cup-shaped appearance in the negative-stain TEM with HSP 70, CD63, CD81, CD9, LAMP1, and TSG101 as characteristic markers, suggesting that the vesicular secretome that was isolated also comprised exosomes.…”
Section: Discussionmentioning
confidence: 89%
“…[ 24 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The remaining studies used nanotubes, nanoclusters, nanosheets, as well as dendrimers [ 26 , 49 , 50 , 51 ]. As for the characteristics of NMs, only six of the studies analyzed and reported the zeta potential, two reported the polydispersity index, four analyzed the presence of contaminants (e.g., endotoxins as relevant for immune effects), and three reported the purity as quality control of the NMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs from various biological sources can be modified after isolation when cell-derived exosomes are unable to meet the requirements. While preserving the membrane integrity of exosomes, functional fluorescent tags 102 , imaging probes 103 , immuneactivators 104 , and targeted therapeutic agents can be added 105 . Modified EV surface structures allow in vivo imaging and tracking of EVs.…”
Section: Modification Of Evs For Targeted Deliverymentioning
confidence: 99%